Expression of Vascular Endothelial Growth Factor in Uveal Melanoma - V. G. Likhvantseva; O. A. Anurova; S. E. Astakhova; M. V. Vereshchagina; V. E. Ovanesyan; E. V. Stepanova (Oftalʹmologiâ)
A prerequisite for the growth, progression and metastasis of malignant tumors of any localization is the development of its own vascular network. Newly formed vessels not only nourish the primary tumor, but also create conditions for the spread of tumor cells through the circulatory system and the formation of distant metastases. Angiogenesis is able to launch a small population of tumors from 100–300 cells that have accumulated genetic aberrations and have begun to express proangigenic molecules. The phenomenon is known as “transformation of tumor cells into angiogenic phenotype”. A tumor with angiogenic phenotype carries a high potential for proliferation and malignization. This pattern has been found in many types of cancer, but studied less in uveal melanoma. Meanwhile, in this aspect, uveal melanoma, metastasizing exclusively in a hematogenic way, with its selective, organotropic nature of metastasis, becomes an attractive model for the study of the molecular “scenario” of tumor angiogenesis studies allow us to say that, UM is subject to the general patterns of the development of malignant tumors. As with many types of tumors, VEGF is an obligate condition for the development and progression of UM. The VEGF molecule’s producers in UM are two cell populations: endothelial vascular cells and tumor cells. VEGF’s expression in UM is cyclical. The cycle is re-initiated, apparently, by increasing cell density in tumor proliferate and the development of hypoxia zones. We found no correlation between the intensity of pigmentation, necrosis, hemorrhage, germination in the corner of the front chamber, ophthalmohypertension on the one hand, and expression of VEGF in UM cells on the other. At the same time, a direct link between the expression of VEGF in tumor cells and EC vessels on the one hand and the thickness, base diameter, as well as the localization of UM, on the other hand, has been revealed. Additionally, VEGF expression in tumor cells was closely correlated with the histological structure of UM, and VEGF expression in EC correlated with the stage of the disease. Thus, the authors showed that UM, like other malignant solid tumors, is prone to transformation into angiogenic phenotype and expression of VEGF.